2022
DOI: 10.1038/s41598-022-26580-6
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of circulating donor-derived extracellular vesicles in kidney transplant recipients

Abstract: Extracellular vesicles (EVs) are tissue-specific particles containing valuable diagnostic information. However, single EV analysis in blood is challenging due to their physical properties, the molecular complexity of plasma, and a lack of robust data interpretation methods. We assess the applicability of our recently-developed calibrated Imaging Flow Cytometry (IFCM)-based methodology to detect/characterize circulating tissue-specific EV subsets in the clinical setting of kidney transplantation. Platelet-poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…In biomarker studies, for example, there may be no need to separate or concentrate EVs from a biological matrix if sufficient specificity and sensitivity are reached with the unfractionated sample. In some cases, EVs can also be analysed specifically and directly in a biological fluid (Duijvesz et al., 2015 ; Woud et al., 2022 ). However, to show exclusive EV association of a proposed biomarker or function, separation may be required in the first instance, and further guidance on this is provided here.…”
Section: Ev Separation and Concentrationmentioning
confidence: 99%
“…In biomarker studies, for example, there may be no need to separate or concentrate EVs from a biological matrix if sufficient specificity and sensitivity are reached with the unfractionated sample. In some cases, EVs can also be analysed specifically and directly in a biological fluid (Duijvesz et al., 2015 ; Woud et al., 2022 ). However, to show exclusive EV association of a proposed biomarker or function, separation may be required in the first instance, and further guidance on this is provided here.…”
Section: Ev Separation and Concentrationmentioning
confidence: 99%
“…IFCM acquisition was performed on an ImageStreamX Mark II imaging flow cytometer (ISx; Cytek Biosciences, Fremont, CA, USA) using INSPIRE ® software (version 200.1.0.765; Cytek Biosciences) as reported previously for measuring unprocessed urine and plasma. 21 , 23 Purified uEVs were measured with the same acquisition protocol as urine and cell supernatant. In brief, the settings of INSPIRE ® were: flow speed velocity of 40 mm/s, 6 μm diameter of the flow core, 60× magnification, 405-nm laser at channel 01 (Ch01) with power: 120 mW, 488-nm laser at channel 02 (Ch02) with power: 200 mW, 642-nm laser at channel 05 (Ch05) with power: 150 mW, 785-nm laser for exciting side scatter (SSC) at channel 06 (Ch06) with power: 1.25 mW, and channel 04 (Ch04) used for presenting bright field.…”
Section: Methodsmentioning
confidence: 99%
“…Sample quantification was performed using Amnis IDEAS software (version 6.2; Cytek Biosciences). 21 , 23 In brief, to ensure the quantification of single EVs, the following gating strategy was used: 1) particles with SSC intensities ≤ 5279 a.u., corresponding to EVs ≤ 1200 nm based on calibration, were selected; 2) only singlets were selected and objects with multiple fluorescent spots excluded; 3) A-F particles in unprocessed urine samples were excluded; 4) finally, gating was performed for single- and double-positives based on unstained, isotype-stained, and single-stained samples.…”
Section: Methodsmentioning
confidence: 99%
“…The authors found that mice with AR showed a decrease in donor EVs and an increase in T-cell EVs from the recipient. The potential of donor EVs as biomarkers of rejection has previously received attention in a kidney transplant model, where CD9+ HLA-A3+ EVs from the donor increased only in recipients with no allograft dysfunction [ 88 ]. Furthermore, they found four proteins that were overexpressed in mice with induced AR compared with controls.…”
Section: Evs As Diagnostic Tools In Solid Organ Transplantationmentioning
confidence: 99%